Two Different States of Copper Ions in Zeolites; Advanced Materials Research : Advanced materials, synthesis, development and application; Vol. 880 : Prospects of Fundamental Sciences Development (PFSD-2013) - Efimov A.; Pestryakov A. N. Aleksey Nikolaevich; Espinosa M. Á. H.; Chávez Rivas F.; Petranovskii V. (Diagnostics and Engineering of Novel Materials, 2014)
Title screen